2003
DOI: 10.1002/jrs.981
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of lucigenin on Ag nanoparticles studied by surface‐enhanced Raman spectroscopy: effect of different anions on the intensification of Raman spectra

Abstract: The normal Raman and surface-enhanced Raman spectra of acridine derivative lucigenin were analysed on Ag colloid. The effect of different anions on the adsorption mechanism of this molecule was also investigated under different experimental conditions, i.e. excitation wavelength and adsorbate concentration, in order to study the different adsorption of the molecule on the metal under different conditions. The adsorption of lucigenin, which is under the dicationic form, changes depending on the anion added to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…These adsorptions are possible by the formation of a strong ionic pair a nitrogen atom with the anion (in this case chloride) previously adsorbed onto the metal, as also observed for other cationic species. [25][26][27] The interaction of the protonated N atom of BIZ with Cl -seems to be so strong that a CT occurs between the chloride and BIZ in acidic conditions. 28 When the H2SO4 or HNO3 solution was used instead of HCl, the SERS spectrum was not enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…These adsorptions are possible by the formation of a strong ionic pair a nitrogen atom with the anion (in this case chloride) previously adsorbed onto the metal, as also observed for other cationic species. [25][26][27] The interaction of the protonated N atom of BIZ with Cl -seems to be so strong that a CT occurs between the chloride and BIZ in acidic conditions. 28 When the H2SO4 or HNO3 solution was used instead of HCl, the SERS spectrum was not enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works we have demonstrated that LG can attach strongly a metal surface in the presence of anions of different nature in the medium [26,27]. The presence of halides is important to ensure the interaction of quaternary ammines onto the metal surface [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…The adsorption of methyl-viologen on metallic surfaces has already been studied on electrodes due to the special electrochemical behavior of these molecules [40]. This interaction is so strong in the case of the bis-acridinium dye lucigenin that a structural change in the environment of N atoms occurs [41,42].…”
Section: N-containing Adsorbatesmentioning
confidence: 99%